2021
DOI: 10.1007/s40123-021-00362-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Landscape of Macular Disorders in Indian Patients with the Advent of Razumab™ (World’s First Biosimilar Ranibizumab): A Comprehensive Review

Abstract: Ranibizumab is approved for the treatment of several macular disorders, including wet age-related macular degeneration (wet AMD), diabetic macular edema (DME), retinal vein occlusion (RVO) and myopic choroidal neovascularization (mCNV), among others. The unaffordability of the innovator ranibizumab among patients from developing countries such as India led to the development of the world’s first biosimilar ranibizumab, which is a cost-effective alternative that does not compromise efficacy and safety. Razumab™… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…32 The efficacy and safety of biosimilar ranibizumab in retinal diseases such as wet AMD, DME, RVO and mCNV have been reported in several prospective and retrospective studies in Indian patients. 33 The real-world efficacy and safety of biosimilar ranibizumab in retinal diseases was reported in the RE-ENACT (n=561) and RE-ENACT 2 (n=341) studies. 33 In this current study, the mean BCVA and CSFT showed significant improvements (p<0.0001) in the visual acuity and disease condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 The efficacy and safety of biosimilar ranibizumab in retinal diseases such as wet AMD, DME, RVO and mCNV have been reported in several prospective and retrospective studies in Indian patients. 33 The real-world efficacy and safety of biosimilar ranibizumab in retinal diseases was reported in the RE-ENACT (n=561) and RE-ENACT 2 (n=341) studies. 33 In this current study, the mean BCVA and CSFT showed significant improvements (p<0.0001) in the visual acuity and disease condition.…”
Section: Discussionmentioning
confidence: 99%
“…33 The real-world efficacy and safety of biosimilar ranibizumab in retinal diseases was reported in the RE-ENACT (n=561) and RE-ENACT 2 (n=341) studies. 33 In this current study, the mean BCVA and CSFT showed significant improvements (p<0.0001) in the visual acuity and disease condition. Also, the percentage of patients with IRF and SRF significantly reduced from baseline to week 48 for all indications after biosimilar ranibizumab treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16.2.80 touchREVIEWS in Ophthalmology sustainable option; biosimilars have an expected high implementation rate, at least in developing countries, though usage in the United States remains to be seen. 5 While biosimilars have only recently entered the ophthalmology scene, biosimilars have successfully been integrated into other medical specialties, such as oncology and dermatology, with the first biosimilar approved by the FDA in 2015. 6 Multiple studies have investigated the use of biosimilars in a variety of retinal conditions, including NvAMD, DMO and mCNV, which this review will cover.…”
mentioning
confidence: 99%